(untitled) (Archive of Conferences, 2021)
In this article, gaming activity is considered as one of the factors in the formation of a healthy lifestyle culture. The role of the characteristic features of the game process in the formation and organization of a healthy lifestyle culture is recognized. The importance of physical exercise and sports for human health was discussed.